Androgen Receptor is Expressed in Breast Cancer Brain Metastases. Issue 10 (November 2021) - Bergen, Elisabeth S.; Berghoff, Anna S.; Steindl, Ariane; Rajky, Orsolya; Mercea, Petra A.; Kiesel, Barbara; Tendl-Schulz, Kristina; Bago-Horvath, Zsuzsanna; Exner, Ruth; Fitzal, Florian; Dieckmann, Karin; Widhalm, Georg; et al.
Abstract : Background: Androgen receptor (AR) expression is a potential therapeutic target in breast cancer (BC) as it is frequently expressed in the luminal A and B subtypes and in approximately one third of basal-like cancers. As AR-positive BC displays a distinct biological behavior, we aimed to analyze AR expression in the particular context of BC brain metastases (BM). Materials and Methods: Patients with newly diagnosed BC BM treated with neurosurgical resection were identified from the Vienna Brain Metastasis Registry and clinical data including patient characteristics, biological tumor subtypes and overall survival were obtained by retrospective chart review. Formalin-fixed and paraffin-embedded specimen containing BM tissue were retrieved from the Neuro-Biobank. Immunohistochemical staining of AR was performed and AR expression in the tumor-cell nucleus was evaluated. Results: Fifty-seven BM samples from 57 individual patients with BC were available for this analysis. AR expression of ≥1% tumor cells was evident in 20/57 (35.1%) BM specimens; the median AR-expression rate was 10% (range: 1% to 60%). AR expression was observed in 11/21 (52.4%) BM of the luminal/human epidermal growth factor receptor 2 (HER2)-negative subtype, 3/13 (23.1%) of the luminal/HER2-positive subtype, 2/7 (28.6%) of the HER2-positive subtype and 4/16 (25.0%) of the triple-negative subtype ( P =0.247). Median survival from diagnosis of BM was 10 months (range: 0 to 104 mo) in the entire cohort. No significant association of overall survival and AR expression ≥1% was observed (15 vs. 13 mo; P >0.05). Conclusion: AR is expressed in more than one third of BC BM with the highest rates among the luminal/HER2-negative BC subtype and may therefore be a potential prognostic and predictive biomarker in this particular BC population.